Overweight and obese status in children with autism spectrum disorder and disruptive behavior. (May 2018) - Criado, Kristen K; Sharp, William G; McCracken, Courtney E; De Vinck-Baroody, Oana; Dong, Liansai; Aman, Michael G; McDougle, Christopher J; McCracken, James T; Eugene Arnold, L; Weitzman, Carol; Leventhal, John M; Vitiello, Benedetto; et al.
Overweight and obesity are common in pediatric populations. Children with autism spectrum disorder and disruptive behavior may be at higher risk. This study examined whether children with autism spectrum disorder and disruptive behavior are more likely to be overweight or obese than matched controls. Baseline data from medication-free children with autism spectrum disorder who participated in trials conducted by the Research Units on Pediatric Psychopharmacology Autism Network (N = 276) were compared to 544 control children from the National Health and Nutrition Examination Survey database matched on age, sex, race, parent education, and era of data collection. The mean age of the children with autism spectrum disorder was 7.9 ± 2.6 years; 84.4% were males. In the autism spectrum disorder group, the prevalence was 42.4% for overweight and 21.4% for obesity compared to 26.1% for overweight and 12.0% for obesity among controls (p < 0.001 for each contrast). Within the autism spectrum disorder sample, obesity was associated with minority status and lower daily living skills. These findings suggest that children with autism spectrum disorder and disruptive behavior are at increased risk for obesity and underscore the need for weight management interventions in this population.